Ethnomedicinal plants for prevention of cardiovascular diseases in Bangladesh (Bangladesh Journal of Plant Taxonomy, 2019)
Cardiovascular diseases (CVD) are the major causes of death globally. The treatment of CVD by using modern medicines is very expensive. The present article mainly focuses the ethnomedicinal plants used by the local people for the prevention of cardiovascular diseases in Bangladesh. Information on the ethnomedicinal uses of plants was collected using semi-structured interviews with key informants during the year of2017 and 2018. Group discussion with local people was also conducted for the promotion of data collection. A total of 41 medicinal plant species was recorded for the prevention of cardiovascular diseases. These species belong to 30 families. The most frequently used medicinal plant species for the prevention of cardiovascular diseases were Terminalia arjuna (Roxb. ex DC.) Wight & Arn., Terminalia bellirica (Gaertn.) Roxb., Terminaliachebula Retz., Allium sativum L., Tamarindus indica L. and Alternanthera sessilis (L.) R. Br. ex Roem. Informant consensus factor (Fic) has been calculated to determine the agreement of local people in the use of medicinal plants for the CVD. Among the ailments categories high Fic value was found in case of antioxidant followed by heartache, high blood pressure and blood purifier. Comparing with previous research Hylocereus undatus (Haw.) Briton and Rose, Alternanthera paronychioides Klotzsch ex Koch and Lactuca sativa L. were seem to be newly reported medicinal plants for the prevention of cardiovascular diseases in Bangladesh. The plant species with high citation, Fic and Fl values can be subjected to phytochemical investigation to find new class of active compounds for the treatment of cardiovascular diseases. The findings of the present study are very preliminary. Further long term studies are needed to validate the ethnomedicinal plants used by the local people for the prevention of cardiovascular diseases in Bangladesh.